Anonymous witnesses and the accused's right to a fair trial - Hlib Rybalko (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2023)
Introduction. The article examines the question of the questioning of anonymous witnesses, the use of their testimony at the stage of the trial in the context of the suspect’s or accused’s right to a fair trial. The criteria that allow to make a decision on granting anonymity to a witness in criminal proceedings are defined and three categories of anonymous sources are distinguished, such as statements of absent witnesses, statements of anonymous witnesses, statements of hidden or classified witnesses.